Fault Tree Analysis Untuk Meningkatkan Kualitas Produk - Bambang Suhardi (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2004)
Nowdays the competition on business field is so tight. Companies compete to be the winner on that competition. Competition is done by increase the quality of their product. Because now is the era of quality. All business units have to find lagged indicator, leading indicator and sub leading indicator from their business. All that indicators are arranged become fault tree. In order that the model can be used as a tool to control the process, so its better that fault tree is developed become fishbone diagram.